2020
DOI: 10.1542/peds.2020-1235
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in 17 Italian Pediatric Emergency Departments

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 20 publications
6
69
0
5
Order By: Relevance
“…Children have been mostly overlooked during this pandemic, since the clinical course of COVID-19 in this group is much milder than in adults (4). However, there is an increasing evidence that restrictive measures aimed at limiting the pandemic are having a significant impact on child’s mental health (5).…”
Section: Discussionmentioning
confidence: 99%
“…Children have been mostly overlooked during this pandemic, since the clinical course of COVID-19 in this group is much milder than in adults (4). However, there is an increasing evidence that restrictive measures aimed at limiting the pandemic are having a significant impact on child’s mental health (5).…”
Section: Discussionmentioning
confidence: 99%
“…However, if such a differences between sexes is present in the pediatric population has never been analyzed yet. Major pediatric papers mainly focused age as a risk factors of disease severity but, to our knowledge, no sub-analyses assessing sex have been described (9)(10)(11)(12)(13)(14)(15). Since sex-hormones or specific habits (alcohol, type-2 diabetes, cardiovascular disease) are less pronounced in the pediatric population, in particular in infants and young children, such an analyses can provide indirect evidence of influence of hormones on COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Initial data from the Chinese Center for Disease Control and Prevention which evaluated case series of 2143 pediatric patients with COVID-19 showed that although the majority of cases had mild or no symptoms, severe and critical cases were present in 10.6%, and 7.3%, for the age groups <1 and 1-4 years [26], and a large US study revealed that children may be a potential source of contagion in the SARS-CoV-2 pandemic even in the absence of symptoms [27]. Two Italian descriptive studies during the rst months of the pandemic reported respectively that 8.5% had moderate disease, 8.5% had a severe disease and 6.9% had a critical presentation [28] and that 43% had been hospitalized, con rming that, although severe cases are rare, children may represent a source of viral transmission [29].…”
Section: Discussionmentioning
confidence: 98%